Freedom for Spain! / Charles Duff, Mauri Codina, Arturo Barea, Edith Moore, García Pradas, W. Carrillo - Duff, CharlesMauri Codina, AlfonsoBarea, Arturo (1897-1957) Moore, Edith (fl. 1941-1944) García Pradas, J.Carrillo, Wenceslao (1889-1963)
Datos tomados de la cubierta